ATRT-39. TRANSCRIPTIONAL ANALYSIS OF ATRT SAMPLES FROM LONG-TERM SURVIVORS AND MATCHED PRIMARY/RECURRENT PAIRS. Issue 2 (22nd June 2018) - Flannery, Patrick; DeSisto, John; Donson, Andrew; Lemma, Rakeb; Vibhakar, Rajeev; Jones, Kenneth; Green, Adam
Abstract: INTRODUCTION: Atypical teratoid/rhabdoid tumor (ATRT) comprises 20% of all brain tumors in children less than 3 years old and is incurable at recurrence. The aim of our study is to determine transcriptional differences that may predict recurrence and raise more effective therapeutic strategies at recurrence. METHODS: We performed microarray RNA expression profiling on three primary ATRT samples from long-term recurrence-free survivors (two from the SHH and one from the MYC epigenetic subgroup) and three sets of matched primary and recurrent patient ATRT samples (two MYC and one SHH). RNA-Seq was also performed on the primary/recurrent sets. We conducted clustering and geneset enrichment analysis (GSEA) on the microarray data. RESULTS: Clustering analysis identified two subgroups, with the first group containing the three non-recurrent tumors and the six samples from the primary/recurrent pairs in the second (coph=1.0). GSEA demonstrated upregulation of the Myc oncogenic pathway (Hallmark Myc geneset, NES=1.53, FDR=0) and upregulated tumor invasion pathways (Hallmark EMT geneset, NES=1.0, FDR=0.09) in primary tumors that recurred compared to those that did not. In recurrent tumors versus their primary pairs, GSEA showed upregulation of Myc pathway genes (Hallmark Myc geneset, NES=3.68, FDR=0), epigenetic regulators (BMI1 geneset, NES=3.15, FDR=0), and neuronal genes (NES=2.93, FDR=0.0), and downregulation of PTEN (NES=2.36, FDR=0.002). CONCLUSIONS/CURRENT WORK: Primary ATRTs that will eventually recur show upregulation of genes associated with oncogenesis and tumor invasion as compared to non-recurrent tumors. At recurrence, these tumors show further upregulation of Myc pathway genes. RNA-Seq analysis is currently in process.